Ultrafast excited-state deactivation dynamics of cyclotrisazobenzene: a novel type of UV-B absorber - Slavov, Chavdar; Yang, Chong; Dreuw, Andreas (ChemPhysChem, 2017)
Azobenzenes are widely utilized as molecular photoswitches for control of nanoscale processes. Their photoisomerization reaction is highly robust and is retained even in extremely rigid systems. Currently, it is not clear what geometric restrictions are required to block this isomerization successfully. We present here a combined experimental and theoretical study on the ultrafast dynamics of cyclotrisazobenzene (CTA) and demonstrate that the structural constraints in CTA prevent isomerization of the photoswitch units. In the developed molecular picture, the N=N bonds respond elastically to the motion along the isomerization coordinates, which leads to ultrafast and complete dissipation of the UV excitation as heat. Based on this property, CTA and possibly other similarly designed molecules can be utilized as UV absorbers, for example in sunscreens; other potential applications are also envisioned.